Inherent duality of vesiculation kinematics revealed through 4D imaging - Mathieu Colombier; Francisco Cáceres; Janine Birnbaum; Rebecca deGraffenried; Yan Lavallée; Jackie E. Kendrick; Bettina Scheu; Simon Thivet; Pedro Valdivia; Ruben M. Ruhekenya; Christian M. Schlepütz; Jonathan M. Castro; et al. (Journal of Volcanology and Geothermal Research, 2026)

Confocal Scanning Laser Microscopic (CSLM) characterization of volcanic rocks - Daniel Weller; Mathieu Colombier; Francisco Cáceres; Jérémie Vasseur; Donald B. Dingwell; Bettina Scheu (Journal of Volcanology and Geothermal Research, 2024)

Evidence for deep gas loss in open volcanic systems - Marielle Collombet; Alain Burgisser; Mathieu Colombier; Elizabeth Gaunt (Bulletin of Volcanology, 2021)

Rheological change and degassing during a trachytic Vulcanian eruption at Kilian Volcano, Chaîne des Puys, France - Mathieu Colombier; Thomas Shea; Alain Burgisser; Timothy H. Druitt; Lucia Gurioli; Dirk Müller; Francisco Cáceres; Kai-Uwe Hess; Pierre Boivin; Didier Miallier; Donald B. Dingwell (Bulletin of Volcanology, 2020)
Magma ascent during silicic dome-forming eruptions is characterized by significant changes in magma viscosity, permeability, and gas overpressure in the conduit. These changes depend on a set of parameters such as ascent rate, outgassing and crystallization efficiency, and magma viscosity, which in turn may influence the prevailing conditions for effusive versus explosive activity. Here, we combine chemical and textural analyses of tephra with viscosity models to provide a better understanding of the effusive-explosive transitions during Vulcanian phases of the 9.4 ka eruption of Kilian Volcano, Chaîne des Puys, France. Our results suggest that effusive activity at the onset of Vulcanian episodes at Kilian Volcano was promoted by (i) rapid ascent of initially crystal-poor and volatile-rich trachytic magma, (ii) a substantial bulk and melt viscosity increase driven by extensive volatile loss and crystallization, and (iii) efficient degassing/outgassing in a crystal-rich magma at shallow depths. Trachytic magma repeatedly replenished the upper conduit, and variations in the amount of decompression and cooling caused vertical textural stratification, leading to variable degrees of crystallization and outgassing. Outgassing promoted effusive dome growth and occurred via gas percolation through large interconnected vesicles, fractures, and tuffisite veins, fostering the formation of cristobalite in the carapace and talus regions. Build-up of overpressure was likely caused by closing of pore space (bubbles and fractures) in the dome through a combination of pore collapse, cristobalite formation, sintering in tuffisite veins, and limited pre-fragmentation coalescence in the dome or underlying hot vesicular magma. Sealing of the carapace may have caused a transition from open- to closed- system degassing and to renewed explosive activity. We generalize our findings to propose that the broad spectrum of eruptive styles for trachytic magmas may be inherited from a combination of characteristics of trachytic melts that include high water solubility and diffusivity, rapid microlite growth, and low melt viscosity compared to their more evolved subalkaline dacitic and rhyolitic equivalents. We show that trachytes may erupt with a similar style (e.g., Vulcanian) but at significantly higher ascent rates than their andesitic, dacitic, and rhyolitic counterparts. This suggests that the periodicity of effusive-explosive transitions at trachytic volcanoes may differ from that observed at the well-monitored andesitic, dacitic, and rhyolitic volcanoes, which has implications for hazard assessment associated with trachytic eruptions.

Diversity of soluble salt concentrations on volcanic ash aggregates from a variety of eruption types and deposits - Mathieu Colombier; Sebastian B. Mueller; Ulrich Kueppers; Bettina Scheu; Pierre Delmelle; Corrado Cimarelli; Shane J. Cronin; Richard J. Brown; Manuela Tost; Donald B. Dingwell (Bulletin of Volcanology, 2019)